Awareness of Alcohol among Adolescents and Young Adults of Mangalore - D'SA, Joswin Rakesh; Shetty, Seemitha; V., Shahina; Sahu, Shashank; Prabhakar, Shifali; Kundapur, Rashmi; Kiran, K. G. (Journal of Health and Allied Sciences NU, 2016)
Introduction: Alcohol consumption is a major public health problem in most parts of the world responsible for 3.2per cent of deaths (1.8 million). Prevalence of alcohol use in India is reported to be 21.4%. The concern, is that there has been a rapid change in patterns and trends of alcohol use in India, chief among them is people are beginning to drink at ever-younger ages. Alcohol consumption of the students under the age of 18 years is markedly high which needs to be addressed.Aims and Objectives: To assess the awareness of risk factors in alcohol consumption among adolescents and young adults.Materials and Method: Materials used are -Questionnaire pertaining to the awareness of alcohol consumption.Methodology: Assessment of awareness and knowledge of alcohol consumption was done by means of answering a pretested validated questionnaire with anonymity.Results: According to the study done, 67.18% of students knew who consumed alcohol under the age of 18. It was found, 28.03% of the subjects perceived that alcohol consumption started because of the urge to try something new.Conclusion: A high majority of the students are aware of the underage drinking and risk factors associated with it.
Keywords: alcohol; awareness; adolescents